Challenges in lentiviral vector production: retro-transduction of producer cell lines - Klimpel, Maximilian; Obert, Christin; Terrao, Monica; Singh, Parameswari; Wei, Haiyan; Chen, Chao-Guang; Gille, Andreas; Wissing, Silke; Laux, Holger (Frontiers in Bioengineering and Biotechnology, 2025)
The increasing demand for lentiviral vectors (LVs) has led to the development of several stable cell lines and production methods over the last 2 decades in order to increase titers and yields, reduce production costs and improve the safety of the vector product. However, the phenomenon of retro-transduction, which describes the transduction of LV producer cells by self-produced LVs, remains largely unaddressed in the context of LV production. Recent research has focused on various approaches to reduce the impact of retro-transduction on LV yield and process performance. This article reviews existing and new research data that highlights the impact of retro-transduction in LV manufacturing. In addition, a perspective on current advances to reduce retro-transduction is provided and a potential novel strategy called ENV-Y is presented, which could not only reduce the impact of retro-transduction but also facilitate the subsequent LV downstream process.